Diagnostic utility of portal vein pulsatility index in differentiating cirrhotic patients with portal hypertension from healthy controls - Shahria, Afrin; Sultana, Nasim; Monowara, Mahmuda; Sultana, Tania; Mosharof, Bipasha (International Journal of Research in Medical Sciences, 2026)
Background: Cirrhosis is a major global health problem, causing significant morbidity and mortality, and is characterized by progressive hepatic fibrosis that leads to portal hypertension and associated complications such as ascites, hepatorenal syndrome, and hepatic encephalopathy. The purpose of this study was to evaluate the diagnostic accuracy of portal vein pulsatility index in distinguishing cirrhotic patients with portal hypertension from healthy individuals. Methods: This cross-sectional study was conducted at the department of radiology and imaging, Bangladesh Medical University (BMU), Dhaka, Bangladesh, from January 2024 to September 2025, enrolling 60 participants (30 cirrhotic patients with portal hypertension and 30 healthy controls). Doppler ultrasonography was performed after fasting using an Esaote MyLab X8 system, and portal vein pulsatility index (PI) was calculated as (Vmax − Vmin)/Vmax. Disease severity was assessed by Child-Pugh class, and diagnostic accuracy of PI was evaluated using ROC analysis (SPSS v23.0; p<0.05). Results: Among 60 participants (30 cirrhotic, 30 healthy), cirrhotic patients had a significantly lower portal vein pulsatility index (0.15±0.037 versus 0.41±0.044; p<0.001), which decreased with worsening Child-Pugh class (A- 0.19, B- 0.15, C- 0.12; p<0.001). At a cut-off of 0.35, PI showed 96.7% sensitivity, 86.7% specificity, and 91.7% accuracy (AUC 0.968), confirming its value as a non-invasive marker for differentiating cirrhotic patients from healthy controls. Conclusions: Portal vein pulsatility index is a reliable non-invasive marker for identifying cirrhotic patients with portal hypertension.